A Note on the Incidence of Bacillus thuringiensis in Fruit Fly Larvae in the Sudan (University of Khartoum Journal of Agricultural Sciences, 2025)
This study was conducted to investigate and identify the reason for the deathof wild fruit fly larvae in the laboratory. The toxic activity of the presumptive bacterialisolate from fruit fly larvae was examined on the invasive fruit fly Bactrocera invadenslarvae. The isolate was identified as Bacillus thuringiensis (B.t.) on the bases ofmorphological characteristics and biochemical tests. Additionally, the B t. isolate wassent to Poland for more investigations. Over 80% of the treated larvae were dead underroom conditions compared with untreated larvae where no mortality was recorded aftereight days. Furthermore, symptoms of the infection appeared on the body of treatedlarvae, while no symptoms appeared on untreated larvae.